Improving health service delivery for women with diabetes in pregnancy in remote Australia: survey of care in the Northern Territory Diabetes in Pregnancy Partnership. (11th October 2014) - Edwards, Laura; Connors, Christine; Whitbread, Cherie; Brown, Alex; Oats, Jeremy; Maple‐Brown, Louise; the NT Diabetes in Pregnancy Partnership
<x xml:space="preserve">Abstract</x> Background In the Northern Territory (NT), 38% of 3500 births each year are to Indigenous women, 80% of whom live in regional and remote areas. Compared with the general Australian population, rates of pre‐existing type 2 diabetes in pregnancy are 10‐fold higher and rates of gestational diabetes are 1.5‐fold higher among Indigenous women. Current practices in screening for diabetes in pregnancy in remote Australia are not known. Aims To assess current health service delivery for NT women with diabetes in pregnancy (DIP) by surveying healthcare professionals' views and practices in DIP screening and management. Materials and Methods A cross‐sectional survey of NT healthcare professionals providing clinical care for women with DIP was conducted based on pre‐identified themes of communication, care‐coordination, education, orientation and guidelines, logistics and access, and information technology. Results Of the 116 responders to the survey, 78% were primary healthcare professionals, 32% midwives and 25% general practitioners. High staff turnover was evident: of Central Australian professionals, only 33% (urban) and 18% (regional/remote) had been in their current position over 5 years. DIP screening was conducted at first antenatal visit by 66% and at 24–28‐week gestation by 81%. Only 50% of respondents agreed that most women at their health service received appropriate care for DIP, and 41% of primary care practitioners were neutral or not confident in their skills to manage DIP. Conclusions It is promising that many healthcare professionals report following new guidelines in conducting early pregnancy screening for DIP in high risk women. Several challenges were identified in healthcare delivery to a high risk population in remote Australia.